Il virus, il genere, la cura: una rivoluzione ai tempi del CoViD-19? (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The unexpected and sudden lockdown experience has favoured the emergence in public discourse of certain issues, such as care, which have long been known in feminist debates on gender inequalities. Starting from a clarification of the ambiguities that, albeit unintentionally, the expression “care work” presents, this contribution argues in favour of the intervention of public institutions and the law, in order to overcome the asymmetries in the distribution of tasks that still characterize intra-family relations.
Keywords: Carework; liberty; feminism; inequalities; public institutions and law